2011
DOI: 10.1097/nur.0b013e318234897b
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' Recognition of Delirium in the Hospitalized Older Adult

Abstract: Findings provide further support for the significance of nurses' underrecognition of delirium in the hospitalized older adult when using the CAM. Additional research is warranted regarding the clinical decision-making processes that nurses use in assessing acute cognitive changes and in identifying strategies to improve delirium recognition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
98
4
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(106 citation statements)
references
References 38 publications
1
98
4
3
Order By: Relevance
“…9 The researchers examined the rate of agreement and disagreement between 4 researchers and a sample of 167 nurses in rating for delirium using the CAM. 9 The nurses were only able to detect delirium 25% of the time.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…9 The researchers examined the rate of agreement and disagreement between 4 researchers and a sample of 167 nurses in rating for delirium using the CAM. 9 The nurses were only able to detect delirium 25% of the time.…”
Section: Literature Reviewmentioning
confidence: 99%
“…7 Similar cognitive deficits and behavioral symptoms associated with both delirium and dementia make it difficult to distinguish between the 2. 8 A study conducted by Rice et al 9 showed that delirium in the presence of underlying dementia is underdiagnosed a majority of the time. 9 Patients with delirium typically exhibit acute-onset confusion that fluctuates to periods of lucidity and resolves with the treatment of the underlying cause.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Delirium, which is associated with longer hospital stays and poorer outcomes, is often underrecognized by nurses (Rice et al, 2011). Functional decline among hospitalized patients is estimated to be 50% (Gill, Allore, Gahbauer, & Murphy, 2010).…”
Section: Educating Nurses In Gerontologymentioning
confidence: 99%
“…10 This is thought to be a particularly pressing need given the widespread concern that currently, many patients with delirium are missed, particularly by palliative care nurses, and thus receive inadequate care. [26][27][28][29] In order to comprehend and to address this issue, we require a stronger understanding of how nurses and other caregivers construct their daily practice. To date, studies appear to reflect that nurses too often fail to identify the core features of delirium in their patients, and that they fail to make use of the notion of delirium in their clinical language and reasoning, thus rendering their mental status assessments superficial and unhelpful.…”
Section: David Kenneth Wright Et Almentioning
confidence: 99%